(untitled) (Research, Society and Development, 2022)
Introduction: the sporting context requires from the individuals involved an ability to manage stressful situations in which they are exposed. Technicians operate in an environment that places a lot of pressure on them. Thus, stress manifests itself in everyday life as a factor that can put psychological and physical health at risk. Objective: to analyze the influence of the perception of quality of life and stress on the sense of coherence in sports coaches. Methodology: There were 137 sports coaches from clubs and/or school teams in the city of Aracaju, of both sexes, with a mean age of ± 36.5 years, who answered the Antonovsky questionnaires, the Stress Symptoms Inventory for Adults of Lipp and the SF-36 Health Status Questionnaire. Result: we highlight 60.3% (n=83) of the technicians did not present the symptoms of stress. There was a moderate and inversely proportional correlation (r= - 0.412, p ≤ 0.001) between SC and Stress. It was possible to identify a weak correlation between SC and emotional aspects (r= 0.289, p ≤ 0.001); mental health (r= 0.278, p ≤ 0.001) and physical aspects (r= 0.219, p ≤ 0.05). However, between SC and Pain (r= 0.432, p ≤ 0.001); General state (r= 0.532, p ≤ 0.001) and Social Aspects (r= 0.555, p ≤ 0.001) we observed a moderate and directly proportional correlation. Conclusion: stress and some domains of quality of life such as pain, general condition and social aspects are relevant for determining the sense of coherence in sports coaches.